d-Dimensional KPZ equation as a stochastic gradient flow in an evolving landscape : interpretation and time evolution of its generating functional - Wio, Horacio Sergio (2017)
Fil: Wio, Horacio Sergio. Universidad de Cantabria. Instituto de Física de Cantabria; España.